Original articleTrans-hepatic technique and intraluminal Pulsed Dose Rate (PDR-BT) brachytherapy in treatment of locally advanced bile duct and pancreas cancer - Skowronek, Janusz; Sowier, Aleksander; Skrzywanek, Paweł (Journal of Contemporary Brachytherapy, 2009)
Purpose: To assess the feasibility of intraluminal palliative Pulsed Dose Rate (PDR-BT) brachytherapy in the treatment of locally advanced bile duct and pancreas cancer. Material and methods: Forty-eight patients with advanced bile duct or pancreas cancer, disqualified from surgery or radical external beam radiation therapy (EBRT), were treated with trans-hepatic technique and intraluminal PDR-BT: 29 patients with bile duct cancer and 19 – pancreas cancer. Forty-four patients were treated exclusively with PDR-BT, 4 with PDR–BT and concomitant chemotherapy or surgery. Percutaneous trans-hepatic technique was used to implant the catheter into bile ducts. Most of patients (38/48, 79%) received 25 pulses of 0.8 Gy hourly with the total dose of 20 Gy. In 8 cases PDR was repeated after one week. Target volume encompassed tumor visualized at cholangiography with one or two cm margin measured proximally and distally. Dose was prescribed at 10-15 mm from the source axis. Results: In all cases trans-hepatic technique allowed insertion of BT catheter into bile duct and safe application of PDR-BT. In 19 out of 29 (65.5%) of bile duct cancer cases and in 10 out of 19 (52.6%) of pancreas cancer patients clinical improvement (decrease of jaundice) was noted in first control after 4 weeks. Median overall survival time (OS) for bile ducts cancer patients was 11.2 months and for pancreas cancer patients – 5.2 months. Conclusions: 1. It has been established, that the use of PDR-BT was feasible and had a low early complication rate. A new percutaneous trans-hepatic technique allowed the treatment (insertion of catheter, PDR brachytherapy) to be performed in one day. 2. In most cases a satisfied palliative effect was achieved, however it was more apparent in bile duct cancer patients then in pancreas cancer patients.